2015
DOI: 10.1016/j.ejphar.2015.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin-induced biphasic regulation of tone in the porcine lower esophageal sphincter

Abstract: The lower esophageal sphincter (LES) plays an important role in coordinated esophageal motility. The present study aimed to elucidate how trypsin affects LES contractility. Porcine LES circular smooth muscle strips were prepared. Contractile responses to trypsin were assessed. Trypsin (300nM) induced a transient contraction. At concentrations of 1μM or higher, trypsin induced biphasic responses, consisting of a transient contraction followed by a transient relaxation. Pretreatment with either 1μM tetrodotoxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…TRPV1 releases substance P (SP), which activates natural killer receptors (NKR) 1/2 to induce contraction in CSM [57]. Tanaka et al [58] concluded that PAR-2 induces the activation of Rho-associated protein kinase (ROK), p38 mitogen-activated protein kinase (p38 MAPK) and extracellular signal-regulated protein kinase (ERK) 1/2. ROK is involved in the contractile function of CSM, whereas ROK, p38 MAPK, ERK1/2, and membrane hyperpolarization are involved in relaxation.…”
Section: Trypsinmentioning
confidence: 99%
“…TRPV1 releases substance P (SP), which activates natural killer receptors (NKR) 1/2 to induce contraction in CSM [57]. Tanaka et al [58] concluded that PAR-2 induces the activation of Rho-associated protein kinase (ROK), p38 mitogen-activated protein kinase (p38 MAPK) and extracellular signal-regulated protein kinase (ERK) 1/2. ROK is involved in the contractile function of CSM, whereas ROK, p38 MAPK, ERK1/2, and membrane hyperpolarization are involved in relaxation.…”
Section: Trypsinmentioning
confidence: 99%